Transformative Tilawah: A Holistic Qur'anic Literacy Framework - Artha, Nursani Awal; Surahman, Cucu; Sumarna, Elan; Mubarokah, Syifa Fatihatul (QiST: Journal of Quran and Tafseer Studies, 2025)
Contemporary Islamic education in Indonesia faces a critical challenge: students master Qur'anic recitation technically but struggle to comprehend, internalize, and apply Qur'anic values in daily life, reflecting a problematic textual-contextual dichotomy in pedagogical practice. This study addresses this gap by developing an Integrated Tilawah Framework-a transformative model of Qur'anic literacy-through thematic analysis of tilawah interpretations across five authoritative tafsir works (Al-Tabari, Ibn Kathir, Al-Qurtubi, Al-Mishbah, Al-Azhar) using Braun & Clarke's Methodology. Analysis of two key verses (Q.S. Al Baqarah:121; Al-Muzzammil:4) identified four integrated dimensions: Authentic Transmission Preservation (16.7%), Deep Meaning Comprehension (41.7%), Spiritual Value Internalization (16.7%), and Transformative Practical Application (25.0%). The framework demonstrates substantial synergy with Paulo Freire's critical literacy theory and Ron Miller's holistic education, offering a paradigm shift from technical-passive toward transformative-active Qur'anic engagement. This synthesis of classical Islamic hermeneutics with contemporary critical pedagogy provides educators a comprehensive, culturally-rooted blueprint for curriculum development in Islamic educational contexts. Expert judgment validation is recommended to confirm implementation feasibility. The findings reveal four core themes: authentic transmission preservation, deep meaning comprehension, spiritual value internalization, and transformative practical application. These themes are synthesized into a hierarchical and cyclical framework that reconceptualizes tilawah as transformative Qur'anic literacy rather than mere recitation. Globally, this framework offers a theoretically grounded and pedagogically operational model that contributes to discussions on religious literacy, critical pedagogy, and holistic education. It provides a transferable reference for Qur'anic education across diverse cultural contexts, promoting faith-based learning that is intellectually rigorous, spiritually meaningful, and socially transformative.